How is the Coping Mechanism, the Function of Adolescent Role in the Implementation of Vaccination of Covid-19 Vaccine Based on Psychological Distress? : Cross-sectional Study - M. Suhron; M.Hasinuddin; Faisal Amir; Siti Sulaiha; M. Fajar Sadiq (Universitas STRADA Indonesia, 2023)
Background: The role of Adolescent in implementing the Covid-19 vaccine is still lacking due to their maladaptive coping mechanisms, as indicated by unstable emotions. Maladaptive coping mechanisms hinder the optimal functioning of adolescent in vaccine implementation. Therefore, improvements in coping mechanisms are needed to enhance the optimal functioning of teenagers in this regard. This shows that the role of teenagers in implementing the Covid-19 vaccine is still low. Purpose: The aim of this research is to examine, using Callista Roy's theory, the relationship between coping strategies and the role of adolescents in implementing the Covid-19 vaccine. Methods: This study's design employed a cross-sectional analytical survey method with a population of 132 and a sample of 127 families utilizing proportionate stratified random. A questionnaire on coping strategies, social roles, and psychological discomfort was employed in this study, and the Spearman Rank test was used to analyze the results. Results: Based on the Spearman's Rank results, there is a relationship between coping strategies, adolescent role function, and psychological pressure in the implementation of the Covid-19 vaccine because the p-value is smaller than 0.05. Conclusion: Coping strategies, adolescent role functions, and psychological pressure have a significant relationship with the implementation of the covid vaccine in adolescents. As a result, it is recommended to maximize the role of adolescents, one of which is by empowering adolescent Vaccine Ambassadors who can serve as a platform for the aspirations of adolescents in the implementation and socialization of vaccines while also supporting it as a government program.